Method for improving photoluminescence quantum yield of Cu < + >-doped metal halide luminescent material
By optimizing the preparation process, Cs2ZnCl4: Cu+glazed emitting materials were prepared by cooling crystallization method, which solved the problem of low photoluminescence quantum yield of Cu+doped zinc-based metal halide luminescent materials in the prior art, and realized photoluminescence The quantum yield has been increased to 69.2%, and the material's stability and efficient luminous performance have been maintained.
Patent Information
- Application Number
- CN202311005841.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing Cu+ doped zinc-based metal halide luminescent materials have low photoluminescence quantum yields, up to only 58%, making it difficult to meet the demand for efficient luminescence.
通过优化制备流程,采用降温析晶法制备Cs2ZnCl4: Cu+青光发射材料,具体步骤包括在空气环境中按化学计量比称取原料,加入浓盐酸和次磷酸,进行搅拌反应,并在缓慢冷却过程中控制晶体的析出,最终使用有机溶剂洗涤和真空烘干得到材料。
The photoluminescence quantum yield of Cu+ doped metal halide luminescent materials has been increased to 69.2%, and has maintained high crystallinity and stability. It is suitable for technical fields such as lighting, display, anti-counterfeiting, detection and sensing.
Smart Images

Figure CN119463856A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic semiconductor luminescent materials, and specifically relates to a method for improving Cu + Method for improving photoluminescence quantum yield of doped Cs2ZnCl4 metal halide luminescent materials. Background Art
[0002] In recent years, the broad spectrum luminescence in low-dimensional metal halide materials has attracted widespread attention from researchers. The dimension of low-dimensional metal halide here is not the control of morphology and size, but refers to the molecular structure level, that is, a unique low-dimensional structure is formed according to the degree of separation of A-site cations and metal halide polyhedrons. In such a "soft" lattice structure, the material forms self-trapped excitons (STEs) after being excited. STEs luminescence has the characteristics of wide spectral bandwidth, large Stokes shift, strong stability, and high luminescence efficiency. At present, most of the low-dimensional metal halide luminescent materials are intrinsic STEs luminescence, and are mainly organic-inorganic hybrids. Both the degree of control freedom and stability are lower than those of all-inorganic materials. Cs2ZnCl4, as an all-inorganic zero-dimensional metal halide that is easy to synthesize, has good chemical stability, and a wide band gap, is a potential excellent carrier for studying the emission characteristics of various tetrahedral coordinated doped ions.
[0003] Zinc-based metal halides have become one of the hot candidate materials for regulating the luminescence of extrinsic STEs due to their special crystal structure and non-luminescent properties. 2- The tetrahedron is surrounded by Cs + ions, forming a unique zero-dimensional structure, and the excitons generated after light excitation are confined in the isolated metal polyhedron structure. A large number of reports have confirmed that doping is an effective means to induce new emission centers and improve the photoluminescence properties of metal halides (Chem. Soc. Rev., 2019, 48,517–539). The solid-phase reaction method is considered to be an effective way to achieve ion doping, but compared with it, the liquid phase method not only requires a low temperature, but also is easy to control the product morphology and its luminescence by regulating the reaction conditions. Liu et al. (J. Mater. Chem. C, 2022, 10, 204–209) prepared Cs2ZnCl4 material by hydrothermal reaction and reported Te 4+ Luminescent properties of STEs doped in Cs2ZnCl4 single crystals. + The photoluminescence quantum yield of doped zinc-based metal halides is only 58% at most (J. Phys. Chem. C 2023, 127,807−815), so there is still much room for improvement in the luminescence efficiency of this type of material. Summary of the invention
[0004] The object of the present invention is to provide a method for improving the performance of Cs2ZnCl4: Cu + Method for determining the photoluminescence quantum yield of cyan emitting materials.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method to improve Cs2ZnCl4: Cu + The method for calculating the photoluminescence quantum yield of a cyan light emitting material comprises the following steps: 1) weighing CsCl, ZnCl2 and CuCl raw materials according to the stoichiometric ratio of the materials, adding concentrated hydrochloric acid, and stirring to dissolve; 2) adding a certain amount of hypophosphorous acid to the mixture obtained in step 1) and mixing evenly; 3) sealing the reaction container, stirring and reacting at a certain temperature for a certain time; 4) adding deionized water to the mixture obtained in step 3) and reacting until all the raw materials are dissolved; 5) stopping heating, placing the reaction bottle on a constant temperature heating table and slowly cooling to room temperature, the product precipitates, washing the reaction product with an organic solvent n-butanol, and vacuum drying to obtain the metal halide Cs2ZnCl4: Cu + Material.
[0007] Preferably, the luminescent material exhibits bright cyan light emission under ultraviolet light excitation, and its maximum photoluminescence quantum yield is as high as 69.2%.
[0008] Preferably, in step 1), in order to ensure the purity and luminous efficiency of the material, the molar ratio is CsCl:(ZnCl2+CuCl) = (1~3):1, preferably 2:1, wherein CuCl:(ZnCl2+CuCl) = (0.05~0.2):1, preferably 0.1:1.
[0009] Preferably, in step 1), the ratio of concentrated hydrochloric acid to (ZnCl2+CuCl) is 5L:1mol.
[0010] Preferably, in step 2), the ratio of hypophosphorous acid to (ZnCl2+CuCl) is (0.5 ~ 2) L:1 mol, preferably 1 L:1 mol.
[0011] Preferably, in step 3), the certain temperature is 80-110 o C, preferably 100°C.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] (1) The cooling crystallization preparation method adopted by the present invention is simple to operate. The entire experimental operation is completed under air environment conditions, the experimental conditions are low, and the required experimental equipment and raw material costs are low.
[0014] (2) The preparation method and post-processing process adopted by the present invention can successfully prepare Cs2ZnCl4: Cu under the condition of unlimited raw material feed ratio. + Luminescent materials, with the highest photoluminescence quantum yield of 69.2%, are currently + Doping with metal halides induces STEs at high levels in luminescent materials.
[0015] (3) The Cu + Small single crystals are obtained by doping metal halide luminescent materials with high crystallinity. They retain high optical properties after washing with low-polarity organic solvent n-butanol and still have good stability after being stored in the air for 3 months. The obtained product has the characteristics of good crystallinity, environmental friendliness, and excellent luminescent properties. It can be used in technical fields such as lighting, display, anti-counterfeiting, detection, and sensing. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is the XRD spectrum of the metal halide material doped with different stoichiometric ratios of CsCl:ZnCl2+CuCl prepared in Example 1, Example 2 and Example 3 of the present invention.
[0017] Figure 2 The Cs2ZnCl4 prepared in Example 3 of the present invention: 0.1Cu + Excitation and emission spectra of the samples.
[0018] Figure 3 The Cs2ZnCl4 prepared in Example 3 of the present invention: 0.1Cu + Fluorescence quantum yield spectrum of the samples.
[0019] Figure 4 Cs2ZnCl4: 0.1Cu + Comparison of emission spectra of samples.
[0020] Figure 5 The Cs2ZnCl4 prepared in Example 3, Example 12, Example 13, Example 14, Example 15 and Example 16 of the present invention: 0.1Cu + Comparison of the fluorescence quantum yield of the sample with the data after 3 months of storage. DETAILED DESCRIPTION
[0021] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
[0022] The present invention optimizes the preparation process and introduces optically active metal ions into the low-dimensional crystal structure with low intrinsic STE luminescence efficiency, thus achieving efficient and controllable extrinsic STE luminescence. + The photoluminescence quantum yield of doped metal halide luminescent materials was increased from the reported highest 58% to 69.2%.
[0023] Embodiment 1:
[0024] Weigh 1 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 35.1%.
[0025] Embodiment 2:
[0026] Weigh 3 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After 1 hour of reaction, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 oC in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 54.6%.
[0027] Embodiment 3:
[0028] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 69.2%.
[0029] Figure 1 For the XRD patterns of the metal halide materials doped with different stoichiometric ratios of CsCl:ZnCl2+CuCl prepared in Example 1, Example 2 and Example 3, all the diffraction peaks match the Cs2ZnCl4 with PDF card number 10-0318, proving that the synthesized materials are pure Cs2ZnCl4 phase.
[0030] Figure 2 To prepare Cs2ZnCl4 in this example: 0.1Cu + The excitation and emission spectra of the sample have the best excitation wavelength and the maximum emission wavelength of 268nm and 490nm respectively, the half-width of the emission peak is about 75nm, and it has broadband cyan emission under ultraviolet light excitation. The photoluminescence quantum yield spectrum is shown in Figure 3 As shown, there is an obvious cyan emission peak, with the highest value being 69.2%.
[0031] Embodiment 4:
[0032] Weigh 2 mmol of CsCl, 0.95 mmol of ZnCl2 and 0.05 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 40.9%.
[0033] Embodiment 5:
[0034] Weigh 2 mmol of CsCl, 0.8 mmol of ZnCl2 and 0.2 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 47.7%.
[0035] Compared with Comparative Example 3, Example 3, Example 4 and Example 5 show that Cu + The optimum doping concentration is 0.1.
[0036] Embodiment 6:
[0037] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 0.5 ml of hypophosphorous acid, seal it and place it on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal it and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool it to room temperature at a cooling rate of 5 ° C / h. Open the glass bottle, pour out the waste liquid, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice according to the same washing method. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 34.1%.
[0038] Embodiment 7:
[0039] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 2 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 48.3%.
[0040] Figure 4 Cs2ZnCl4: 0.1Cu prepared under the conditions shown in Examples 3, 6 and 7 +Comparison of emission spectrum intensity of samples. In addition to the doping content, the amount of hypophosphorous acid also affects the luminescence performance of the material. Comparative Example 2 shows that no luminescence occurs without the addition of hypophosphorous acid, and excessive hypophosphorous acid slightly reduces the luminescence intensity.
[0041] Embodiment 8:
[0042] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 80 ° C and stir for 1 h to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 80 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on an 80 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 38.1%.
[0043] Embodiment 9:
[0044] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 110 ° C and stir for 1 h to fully dissolve the raw materials. After 1 hour of reaction, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 110 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 110 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 oC in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 63.2%.
[0045] Comparison of Example 3, Example 8 and Example 9 with Comparative Example 5 shows that the optimal reaction temperature of the reaction is 100°C.
[0046] Embodiment 10:
[0047] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 2 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 66.6%.
[0048] Embodiment 11:
[0049] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 10 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 27.2%.
[0050] Comparison between Example 3 and Example 10 and Example 11 shows that the optimal cooling rate of the reaction is 5°C / h.
[0051] Embodiment 12:
[0052] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of methanol solution to wash for 1 min, repeat the washing twice, then replace methanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 30.3%, and 15.8% after three months.
[0053] Embodiment 13:
[0054] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of ethanol solution to wash for 1 min, repeat the washing twice, then replace ethanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 45.4%, and 14.4% after three months.
[0055] Embodiment 14:
[0056] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After the reaction for 1 h, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 min so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of isopropanol solution to wash for 1 min, repeat the washing twice, then replace the isopropanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 58.1%, and 31.2% after three months.
[0057] Embodiment 15:
[0058] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of cyclohexanol solution to wash for 1 min, repeat the washing twice, then replace cyclohexanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 41.7%, and 25.4% after three months.
[0059] Embodiment 16:
[0060] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes to completely dissolve the raw materials. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of n-hexane solution to wash for 1 min, and repeat the washing 3 times. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 29.4%, and 9.8% after three months.
[0061] Figure 5The photoluminescence quantum yield (PLQY) of the metal halide luminescent materials prepared in Example 3, Example 12, Example 13, Example 14, Example 15 and Example 16 was compared with the test data three months later. We found that among the commonly used organic solvents, the higher the polarity of the washing solvent, the lower the luminescence efficiency of the product. n-Butanol, which has low polarity and can be miscible with water in a certain proportion, has the least effect on the luminescence performance of the material. The final photoluminescence quantum yield of the product reached a maximum value of 69.2% and had good stability.
[0062] Comparative Example 1:
[0063] Weigh 2 mmol of CsCl and 1 mmol of ZnCl2, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal it and place it on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal it and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool it to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice according to the same washing method. Place the washed sample at 60 o C in a vacuum oven for 12 h, and after the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield testing show that the reaction product obtained in this comparative example does not emit light.
[0064] Comparative Example 2:
[0065] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 hour to fully dissolve the raw materials. After 1 hour of reaction, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 oC in a vacuum oven for 12 h, and after the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield testing show that the reaction product obtained in this comparative example does not emit light.
[0066] Comparative Example 3:
[0067] Weigh 1 mmol of CsCl, 0.99 mmol of ZnCl2 and 0.01 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After 1 hour of reaction, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour off the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 5.2%.
[0068] Comparative Example 4:
[0069] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 0.1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 100 ° C and stir for 1 h to fully dissolve the raw materials. After 1 hour of reaction, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 100 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 100 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 oC in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 9.5%.
[0070] Comparative Example 5:
[0071] Weigh 2 mmol of CsCl, 0.9 mmol of ZnCl2 and 0.1 mmol of CuCl, add them to a 30 ml transparent glass bottle, add 5 ml of concentrated hydrochloric acid, 1 ml of hypophosphorous acid, seal and place on a heated magnetic stirrer. Heat to 60 ° C and stir for 1 hour to fully dissolve the raw materials. After the reaction for 1 hour, add 3 ml of deionized water to the mixture, seal and stir the reaction again at 60 ° C for 10 minutes so that all the raw materials are dissolved. After the reaction is completed, remove the stirrer, place the glass bottle on a 60 ° C heating table, and slowly cool to room temperature at a cooling rate of 5 ° C / h. When the crystals stop precipitating and no longer grow, open the glass bottle, pour out the supernatant, add 3 ml of n-butanol solution to wash for 1 min, repeat the washing twice, then replace n-butanol with n-hexane and wash twice in the same way. Place the washed sample at 60 o C in a vacuum oven for 12 hours. After the temperature drops to room temperature, the sample is collected in a reagent bottle for subsequent testing. XRD testing proves that the product is Cs2ZnCl4. Excitation and emission spectra and fluorescence quantum yield tests show that its photoluminescence quantum yield is 3.7%.
Claims
1. A method to increase Cu + The method for increasing the photoluminescence quantum yield of a metal halide luminescent material by doping Cs2ZnCl4 is characterized in that: The method comprises the following steps: 1) weighing CsCl, ZnCl2 and CuCl raw materials according to the stoichiometric ratio of the materials, adding concentrated hydrochloric acid, heating and stirring; 2) adding a certain amount of hypophosphorous acid to the mixture obtained in step 1) and mixing evenly; 3) sealing the reaction container and continuing stirring for a certain time; 4) adding deionized water to the mixture obtained in step 3) and reacting until all the raw materials are dissolved; 5) stopping stirring, placing the reaction bottle on a constant temperature heating table and slowly cooling it to room temperature, the product precipitates, washing the reaction product with an organic solvent n-butanol and vacuum drying it to obtain a luminescent material.
2. The method according to claim 1, characterized in that The luminescent material exhibits bright cyan emission under ultraviolet light excitation, and its maximum photoluminescence quantum yield is as high as 69.2%.
3. The method according to claim 1, characterized in that In step 1), in order to ensure the purity and luminous efficiency of the material, the molar ratio is CsCl:(ZnCl2+CuCl) = (1~3):1, preferably 2:1, wherein CuCl:(ZnCl2+CuCl) = (0.05~0.2):1, preferably 0.1:
1.
4. The method according to claim 1, characterized in that In step 1), the ratio of concentrated hydrochloric acid to (ZnCl2+CuCl) is 5L:1mol.
5. The method according to claim 1, wherein In step 2), the ratio of hypophosphorous acid to (ZnCl2+CuCl) is (0.5 ~ 2) L:1 mol, preferably 1 L:1 mol.
6. The method according to claim 1, characterized in that In step 3), the certain temperature refers to 80-110 o C, preferably 100°C.